1982
DOI: 10.1063/1.92954
|View full text |Cite
|
Sign up to set email alerts
|

Deep center EL2 and anti-Stokes luminescence in semi-insulating GaAs

Abstract: We have observed efficient photoluminescence upconversion in semi-insulating GaAs. This upconversion is apparently associated with a two-step excitation of the deep level EL2 as indicated by the excitation spectrum. Assessment of these results along with results in the literature suggests that this center is due to an arsenic antisite defect. Line shape analysis indicates that clustering of acceptors occurs near the site of the defect. These results provide insight into the agents responsible for the semi-insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Such UC effects have been reported in bulk semiconductors [3,4], heterostructures [5][6][7][8][9][10][11], and selfassembled quantum dots [12,13]. For UC in bulk semiconductors and heterostructures, the proposed mechanism involves either two-step photoexcitation process [7][8][9]11] or Auger recombination that ionizes carriers to the higher bandgap region where they undergo radiative recombination [5,6,10].…”
Section: Introductionmentioning
confidence: 96%
“…Such UC effects have been reported in bulk semiconductors [3,4], heterostructures [5][6][7][8][9][10][11], and selfassembled quantum dots [12,13]. For UC in bulk semiconductors and heterostructures, the proposed mechanism involves either two-step photoexcitation process [7][8][9]11] or Auger recombination that ionizes carriers to the higher bandgap region where they undergo radiative recombination [5,6,10].…”
Section: Introductionmentioning
confidence: 96%
“…Such UC effects have been reported in bulk semiconductors, 29,30 heterostructures, [31][32][33][34][35][36][37] and self-assembled quantum dots. 38,39 For UC in bulk semiconductors and heterostructures, the proposed mechanism involves either a two-step photoexitation process [33][34][35]37 or an Auger recombination that ionizes carriers to the higher band gap region where they undergo radiative recombination.…”
Section: Introductionmentioning
confidence: 98%
“…From the experimental evidence, it can be ++ shown that EL2a trap is due to antisite defect, AsGa + , formed during the S! post-grown cooling [ 94,99], as will be discussed further in next section.…”
Section: ]mentioning
confidence: 94%